2019
DOI: 10.3390/agronomy9120844
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenotypic and Physiological Markers of Salt Stress Tolerance in Durum Wheat (Triticum durum Desf.) through Integrated Analyses

Abstract: Salinity is one of the most important stresses that reduces plant growth and productivity in several parts of the world. Nine Tunisian durum wheat genotypes grown under hydroponic conditions were subjected to two levels of salt stress (100 and 170 mM NaCl) for 21 days. An integrative analysis revealing the impact of salinity on key phenotypic and physiological marker traits was then conducted. Principal component analysis grouped these traits into three different clusters corresponding to the absence of salt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
(100 reference statements)
0
7
0
2
Order By: Relevance
“…Indeed, wheat genotypes have different potentialities in adapting with salt stress and producing satisfactory grain yield under natural salinity stress conditions. Several researchers demonstrated considerable genetic variations in salinity tolerance in bread wheat using different experimental setups carried out under either controlled or simulated field conditions [ 14 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, evaluating the salt tolerance of field crops should be confirmed until the yielding stage and, most importantly, should be performed under real field conditions, especially when the evaluation of salt tolerance happens in the advanced generation of breeding programs [ 14 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, wheat genotypes have different potentialities in adapting with salt stress and producing satisfactory grain yield under natural salinity stress conditions. Several researchers demonstrated considerable genetic variations in salinity tolerance in bread wheat using different experimental setups carried out under either controlled or simulated field conditions [ 14 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, evaluating the salt tolerance of field crops should be confirmed until the yielding stage and, most importantly, should be performed under real field conditions, especially when the evaluation of salt tolerance happens in the advanced generation of breeding programs [ 14 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eventual effects of salinity on plant performance can be viewed as growth inhibition, leading to biomass reduction, as it was assessed in this study in terms of reduction of plant height, and fresh weight of broad bean plants grown under saline conditions. It was found that in Triticum durum, cultivar shoot length STI and shoot fresh weight STI were reduced in the presence of two salinity levels [16]. Indeed, a gradual increase in STI of all morphological traits with vermicompost treatments was noted, with the highest increase at 10% VC under salt stress.…”
Section: Discussionmentioning
confidence: 95%
“…Bu verilerden Vigor indeksi; " (kök uzunluğu + sürgün uzunluğu) x çimlenme yüzdesi" formülüne göre hesaplanmıştır. Kuraklık stresinin çimlenme yüzdesi, kök ve sürgün uzunluğu ile vigor indeksine etkisini belirlemek üzere, her çeşitte stres ve kontrol uygulamalarına ait ortalama değerler (M stres ve M kontrol ) dikkate alınarak stres tolerans indeksi "STI (%)= [(M stres )/M kontrol ] x 100" hesaplanmıştır (Guellim et al, 2019).…”
Section: Tohum çImlendirme Testiunclassified